Hermeneutika dalam Tafsir Al-Qur’an: Perspektif Dosen Tafsir di Universitas Islam Negeri Sumatera Utara - Puspa Vanilla; Nurliana Damanik (Yayasan Albahriah Jamiah Indonesia, 2026)
The dynamics of employing hermeneutics in Qur’anic exegesis have sparked an epistemological tension between the authority of tradition and the demands for contextual reading within the contemporary landscape of Islamic scholarship. This shift positions hermeneutics not merely as a methodological tool, but as a site of negotiation among the text, the interpreter, and social reality. The study focuses on elaborating the perspectives of tafsīr (exegesis) lecturers at the State Islamic University of North Sumatra regarding the definition of the position, boundaries, and legitimacy of hermeneutics in exegetical practice. A qualitative approach with a phenomenological-hermeneutic orientation was employed—utilizing in-depth interviews, academic observations, and analyses of instructional documents and scholarly publications—followed by analysis through meaning reduction, thematic categorization, and reflective interpretation. The results reveal three primary conceptual patterns: hermeneutics as a critical instrument for reading context; as a complementary method rooted in classical uṣūl al-Tafsīr (principles of exegesis); and as a reflective approach that negotiates the interpreter’s authority. An epistemological foundation is established through the integration of textual reasoning, critical rationality, and historical sensitivity, while interpretive strategies demonstrate a dialectic between normative meaning and contextual significance. The interpreter’s position is rearticulated from a singular authority to a dialogical, intersubjective role. These findings enrich the epistemology of tafsīr by opening up a methodological space that is adaptive, critical, and contextual, thereby addressing the complexities of modern society.